Use of Audiovisual Media to Improve Students' Learning Interest in Elementary School Education - Khairani, Mawar (International Journal of Students Education, 2025)
The use of audio-visual media in Civics learning in elementary schools still faces various challenges, such as the low level of teacher creativity in managing learning and the perception that Civics only relies on memorization. This research aims to examine the effectiveness of using audio-visual media in improving elementary school students' learning outcomes and interest in Civics subjects through a literature review. The results of the literature review show that the use of audio-visual media is effective in increasing elementary school students' interest and learning outcomes in civics subjects. This improvement is reflected in several aspects: 1) Increased motivation and active participation of students in learning, 2) Learning material can be better understood through a combination of audio and visuals that are appropriate to the stage of students' cognitive development, 3) There is a significant increase in academic grades and abilities of students in connecting the material with everyday life. The use of audio-visual media has been proven to help optimize the learning process by increasing students' attention span and facilitating multi-modal learning.